Storms - Simon, Seymour (New York : Morrow Junior Books, 1989)
Presents information on storms, in simple text with illustrations, and describes the atmospheric conditions that help create thunderstorms, hailstorms, lightning, tornadoes, and hurricanes and includes an explanation of how violent weather affects the environment, the land, and the people.
"Mulberry books"--Cover.
Elem. School Library Collection.
School Library Journal starred.
Wilson's Children.
3.9
3.9
Keywords: Storms -- Juvenile literature; Storms; Storms